Comisión Séptima Constitucional Permanente (2021)
The procedure that must be developed in the commissions and in the plenary in the Congress of the Republic is the one stipulated in Law 5 of 1992: Regulations of the Congress of the Republic of Colombia. However, for pedagogical purposes of the Student Congress Model, the implementation of the procedure will have flexibility to achieve the proposed academic objectives. This procedure will be explained extensively in the initial conference, for learning about the need for a legislative procedure. popular representation in making transcendental decisions for a State is an idea that is handled strongly from the Greco-Roman civilizations. It is catalyzed by the French Revolution. There, with the postulates of equality, fraternity and freedom, together with the idea of ​​a united society, a form of power is molded where the people will be able to decide on the course of the nation, leaving aside the absolutist system.